IMPLEMENTASI PENERAPAN GOOD CORPORATE GOVERNANCE PADA PONDOK PESANTREN DI DESA KEDIRI - Sukriati, Sukriati (Nusantara Hasana Journal, 2025)
This study aims to determine the implementation of GCG, the influencing factors, and its impact on the quality of management and public trust in Islamic boarding schools in Kediri Village, West Lombok Regency. This study is a case study of the Nurul Hakim Islamic boarding school in Kediri Village, West Lombok Regency. Preliminary results indicate that GCG implementation in Islamic boarding schools is still limited but has a positive impact on the quality of management and public trust.